Perbandingan Penggunaan Bahan Bakar Pertalite Dan Pertamax Turbo Terhadap Residu Karbon Dan Unjuk Kerja Pada Sepeda Motor Yamaha Byson 2013 - Rayyan Rayyan; Abdul Wahab; Margianto Margianto (UNIVERSITAS ISLAM MALANG, 2019)
This research was conducted with the aim to know how big influence of analysis of fuel research to performance on motorcycle by using fuel of pertalite and pertamax turbo. In the test execution here (1) to know the difference of performance by using fuel of pertalite and pertamax turbo. (2) to find the highest performing fuel from the first turbo fuel and the pertamax turbo.The research method is the definition of literature and experimental methods. This study using f test will be known whether there are significant differences or tidan between the two samples assuming H0 and H1. The type of research used is experimental research. The tools used in this experimental consist of: 4-stroke 1-cylinder engine brand Yamaha byson 2013. Using dyno test equipment and necessary workshop equipment. From the experimental results it is known that the graph of data analysis with the f test is obtained the result that the value of effective power (HP) analysis of research 1, research analysis 2 that is research analysis 2 has greater power than the research analysis 1. Appropriate solution for further test of machine others should use the latest machines in order to achieve excellence in the research need to be tested further on the fuel of pertalite and pertamax turbo to know the better performance. Keywords: pertalite, pertamax turbo, performance, Yamaha byson 2013